Socialization and Implementation in an Effort to Develop Children's Character Through Traditional Games at the Tunas Melati Orphanage Pontianak City - Haetami, Mimi; Anwar, Khairul; Wahyuningsih, Inka; Khusna, Miftakhul; Putri, Marinda Alfiani; Pebriani, Yospin; Suryati, Suryati; Ahmad, Ahmad; Pramudya, Muhammad Angga; Manik, Dwi Lusiana; Wahyudi, Adong; Viani, Ite (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2024)
This activity aims to develop students' character education through traditional games. The method used in implementing Community Service activities is to use the demonstration method which consists of planning, screening, implementation, evaluation, and reporting. Where this activity consists of delivering traditional game activity material indoors and applying traditional game activity material outdoors.  The results of implementing this traditional game-based learning method have been proven through leadership project activities in the form of socializing traditional games. This Leadership Project activity showed high enthusiasm from teachers during theory sessions and students during traditional game practice. This shows that traditional game-based learning methods can be well accepted by teachers and students. From the implementation carried out, it can be concluded that developing children's character through traditional games is very necessary and liked by children. The character values contained in traditional games include religiousness, hard work, togetherness, love of the country, discipline, patience, creativity, and others.